Distinct impact of tropical SSTs on summer North Pacific high and western North Pacific subtropical high. Issue 10 (23rd May 2013) - Yun, Kyung‐Sook; Yeh, Sang‐Wook; Ha, Kyung‐Ja
Abstract: [1] The distinct impact of tropical Indian Ocean (IO) and western Pacific (WP) sea surface temperatures (SSTs) after the El Niño winter has been investigated in relation to the summer North Pacific high (NPH) and western North Pacific subtropical high (WNPSH). After the El Niño winter, warming of the IO leads to a summer eastern Pacific (EP) SST anomaly distinct from the cooling of WP; EP cooling occurs in the extreme IO warming case and EP warming in the WP cooling case. Both the warming of the IO and cooling of the WP are responsible for the development of the WNPSH, whereas the summer EP cooling induces an enhanced NPH, especially if it coexists with IO warming. The IO warming triggers an abrupt termination of the El Niño event by causing the easterly anomaly in the WP, which leads to the coexistence of IO warming and EP cooling during the boreal summer. The tropical EP cooling may change the North Pacific SST anomalies via the atmospheric bridge and consequently strengthen the extratropical NPH. The experimental results, which have been obtained from the use of atmospheric general circulation model, support the distinct roles of EP cooling on the NPH and of IO warming and WP cooling on the WNPSH. This finding suggests that the combined effect of IO warming and EP cooling generates a coupled pattern of NPH and WNPSH. Key Points: IO warming and WP cooling induce the development of the WNPSH IO warming‐related summer EP cooling induces an enhanced NPH IO warming and EP cooling generate a coupled pattern of NPH and WNPSH